Effect of leaves feeding by the extract of capricorn and licorice roots on some growth and yield traits of maize plant (Zea mays L) - Sabr, Mohammed Jamil; Al-Zubaidi, Najm Abdullah (Journal of agricultural, environmental and veterinary sciences, 2017)
A filed experiment is carried، to study the effect of foliar spray on the plants of hibisscus sabdriffa in four concentrations of 0, 5, 10 and 15 g. L-1 and glycyrrhiza glabra extract with four concentrations of 0, 5, 10 and 15 g. L-1 in the growth and produce of Zea Mays L. Baghdad class, according to the design of complete random sectors (R.C.B.D). The results show that the hibisscus sabdriffa extract is 15 g. L-1 gave the highest mean, plant high, Leaf area, dry matter of geran, ear length, the number of grains in per ear, and the plant yield was 189 cm, 714 cm2, 159.0 g.plant-1, 22. 97 cm, 720.0 tablets, and 212.2g, The results show that Glycyrrhiza Glabra root extract with a concentration of 10 g. L-1 gave the highest mean, plant high, Leaf area, dry matter of geran, length of clove, the number of grains in per ear, and the plant yield, was 191.82 cm812.7 cm2, 183.0 g.plant-1, 23.76 cm and 764.9 grains, 277.4 g. The treatment of the interaction between the plant extract of hibisscus sabdriffa and glycyrrhiza glabra the concentration of 15 g. L-1. Hibisscus sabdriffa + 10 g. L -1 glycyrrhiza glabra is the highest average of the studied traits.